ANALISIS YURIDIS PERLINDUNGAN HUKUM TERHADAP KORBAN PEMASUNGAN ORANG DENGAN GANGGUAN JIWA (ODGJ) DALAM PERSPEKTIF HUKUM PIDANA INDONESIA - Indana Frishilya; Mukhlis R; Adi Tiaraputri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Protection of human rights is a form of service that must be carried out by law enforcement officials or security forces to provide a sense of security, both physically and mentally, to victims from threats, harassment, terror and violence from any party. People with mental disorders who are shackled need special protection and handling from the government to protect their rights as humans. The government must ensure that all people with mental disorders are not shackled and cared for properly without discrimination.The purpose of this research is to find out how the juridical analysis of legal protection for victims of confinement of persons with mental disorders in the perspective of Indonesian criminal law and to find out the ideal arrangements related to legal protection for victims of confinement of persons with mental disorders in the perspective of Indonesian criminal law. The research method used in this thesis uses normative legal research methods, namely legal research that examines statutory regulations and legal principles.From the research, there are two main points that can be concluded. First, the juridical analysis of legal protection for victims of shackling of people with mental disorders in the perspective of Indonesian criminal law, namely the incompatibility between one law and another makes the government appear unfair in providing protection to victims of a criminal act of shackling. The law on mental health seems weak and even does not provide special protection to victims of shackling, there is no state interference in protecting their rights. Second, the ideal is very much in accordance with what is aspired or dreamed of or desired. The ideal arrangement must be in accordance with the aspirations of the state, namely to provide protection in accordance with what the community wants, however, the regulations related to the protection of victims of confinement are still not perfect in providing protection to them. Author's suggestion, First, given the poor conditions experienced by victims of shackling, special protection is needed for victims of criminal acts of confinement of people with mental disorders through a clearer legislation.Keywords : Victims, Shackles, People with Mental Disorders